The Relationship Of Parity, Husband Support And Promotion Of Formula Milk With Exclusive Breastfeeding In The Working Area Of The Simpang Empat 1 Health Center In 2024 - Handayani, Pratiwi Sri; Barkinah, Tut; Dewi, Vonny Khresna; Isnaniah, Isnaniah (JURNAL KEBIDANAN BESTARI, 2024)
Exclusive Breastfeeding is breastfeeding to babies without complementary foods and drinks from birth to 6 months of age. However, the coverage of exclusive breastfeeding is still low. Many factors influence, one of the influencing factors is parity, husband support and formula promotion. The purpose of this study is to determine the relationship between parity, husband support, and formula milk promotion with exclusive breastfeeding in the Simpang Empat 1 Health Center Work Area in 2024. This type of research is observational analytical with a cross sectional design, the population of this study is all mothers who have babies aged 7-24 months, as many as 122 samples using the slovin formula, sampling technique with accidental sampling, this study was conducted in January - June 2024. The data analysis of this study was univariate and bivariate analysis using the Chi Square test and the Kolmogorov Smirnov alternative test with a significance of α = 0.05. The results of the study showed a parity relationship with exclusive breastfeeding ρ-value ρ-value 0.049 (ρ < α 0.05), there was a relationship between husband support and exclusive breastfeeding ρ-value 0.000 (ρ < α 0.05), and there was a relationship between formula promotion and exclusive breastfeeding ρ 0.000 (ρ < α 0.05). The conclusion of the study was that the coverage of exclusive breastfeeding was 62.3%, as much as 59.8% of multipara parity, as many as 68.9% of those who received support from their husbands, and 62.3% of whom were exposed to the promotion of formula milk. There is a relationship of parity, husband support and promotion of formula milk with exclusive breastfeeding. Therefore, it is hoped that the Simpang Empat 1 Health Center will be used as a monitoring and evaluation material to increase the coverage of exclusive breastfeeding. Keywords: exclusive breastfeeding, parity, husband support, formula milk promotion.